Planetary Terrestrial Analogues Library project: 2. building a laboratory facility for MicrOmega characterization. (15th November 2020) - Loizeau, Damien; Lequertier, Guillaume; Poulet, François; Hamm, Vincent; Pilorget, Cédric; Meslier-Lourit, Lionel; Lantz, Cateline; Werner, Stephanie C.; Rull, Fernando; Bibring, Jean-Pierre
Abstract: Multiple spectroscopic techniques have been selected on previous, present and forthcoming missions to explore planetary surfaces in the Solar System. In particular, forthcoming ESA/Roscosmos and NASA missions to the surface of Mars will bring instruments capable of near-infrared (NIR), Raman and Laser Induced Breakdown Spectroscopies to analyze the mineralogy and chemistry of rocks. The PTAL (Planetary Terrestrial Analogues Library) project aims at building a multi-instrument spectral database of a large variety of natural Earth rock samples, including Mars analogues. The NIR hyperspectral microscope MicrOmega was selected to characterize the mineralogy of these analogues within the PTAL project. The instrument model used for the PTAL project is a spare flight model that requires specific care. For the safety of the instrument, and because of the large number of samples in the PTAL library and the requirement to optimize the observational conditions, a dedicated and semi-automated setup was built for the use of the MicrOmega instrument for this project. This paper presents the requirements specified for this setup, the technical solutions that have been selected, their implementation and the performances of the set-up. Sample preparation and operations during sample observations are explained, and a characterization example is presented to briefly illustrate the capabilities of MicrOmega in this set-up. The complete results from the MicrOmega characterizations of the PTAL rock analogues will be presented in a forthcoming paper (Loizeau et al. in prep). Graphical abstract: Image 1 Highlights: Building a multi-techniques spectral library to support planetary surface exploration. Use of the NIR hyperspectral microscope MicrOmega requires special laboratory set-up. Set-up allows observation of >10 samples within a day in optimal conditions. Mineralogy can be constrained at microscopic scale on bulk rock samples.